Optimizing cathodoluminescence microscopy of buried interfaces through nanoscale heterostructure design. Issue 20 (3rd May 2022) - Francaviglia, Luca; Zipfel, Jonas; Carlstroem, Johan; Sridhar, Sriram; Riminucci, Fabrizio; Blach, Daria; Wong, Ed; Barnard, Edward; Watanabe, Kenji; Taniguchi, Takashi; Weber-Bargioni, Alexander; Ogletree, D. Frank; et al.
Abstract : Spatial resolution and brightness in cathodoluminescence can be tuned by nanoscale design of samples. Abstract : Mapping the optical response of buried interfaces with nanoscale spatial resolution is crucial in several systems where an active component is embedded within a buffer layer for structural or functional reasons. Here, we demonstrate that cathodoluminescence microscopy is not only an ideal tool for visualizing buried interfaces, but can be optimized through heterostructure design. We focus on the prototypical system of monolayers of semiconducting transition metal dichalcogenide sandwiched between hexagonal boron nitride layers. We leverage the encapsulating layers to tune the nanoscale spatial resolution achievable in cathodoluminescence mapping while also controlling the brightness of the emission. Thicker encapsulation layers result in a brighter emission while thinner ones enhance the spatial resolution at the expense of the signal intensity. We find that a favorable trade-off between brightness and resolution is achievable up to about ∼100 nm of total encapsulation. Beyond this value, the brightness gain is marginal, while the spatial resolution enters a regime that is achievable by diffraction-limited optical microscopy. By preparing samples of varying encapsulation thickness, we are able to determine a surprisingly isotropic exciton diffusion length of >200 nm within the hexagonal boron nitride which is the dominant factor that determines spatial resolution. We further demonstrate that we can overcome the exciton diffusion-limited spatial resolution by using spectrally distinct signals, which is the case for nanoscale inhomogeneities within monolayer transition metal dichalcogenides.